What matters and influence resuscitation preference? Development, field testing, and structural validation of items among older patients in the emergency department - Stine Hanson; Søren Kabell Nissen; Dorthe Nielsen; Annmarie Lassen; Mikkel Brabrand; Roberto Forero; Jens Søndergaard Jensen; Jesper Ryg (BMC Geriatrics, 2022)
Abstract Background Decisions about resuscitation preference is an essential part of patient-centered care but a prerequisite is having an idea about which questions to ask and understand how such questions may be clustered in dimensions. The European Resuscitation Council Guidelines 2021 encourages resuscitation shared decision making in emergency care treatment plans and needs and experiences of people approaching end-of-life have been characterized within the physical, psychological, social, and spiritual dimensions. We aimed to develop, test, and validate the dimensionality of items that may influence resuscitation preference in older Emergency Department (ED) patients. Methods A 36-item questionnaire was designed based on qualitative interviews exploring what matters and what may influence resuscitation preference and existing literature. Items were organized in physical, psychological, social, and spiritual dimensions. Initial pilot-testing to assess content validity included ten older community-dwelling persons. Field-testing, confirmatory factor analysis and post-hoc bifactor analysis was performed on 269 older ED patients. Several model fit indexes and reliability coefficients (explained common variance (ECV) and omega values) were computed to evaluate structural validity, dimensionality, and model-based reliability. Results Items were reduced from 36 to 26 in field testing. Items concerning religious beliefs from the spiritual dimension were misunderstood and deemed unimportant by older ED patients. Remaining items concerned physical functioning in daily living, coping, self-control in life, optimism, overall mood, quality of life and social participation in life. Confirmatory factor analysis displayed poor fit, whereas post-hoc bifactor analysis displayed satisfactory goodness of fit (χ2 =562.335 (p<0.001); root mean square error of approximation=0.063 (90% CI [0.055;0.070])). The self-assessed independence may be the bifactor explaining what matters to older ED patients’ resuscitation preference. Conclusions We developed a questionnaire and investigated the dimensionality of what matters and may influence resuscitation preference among older ED patients. We could not confirm a spiritual dimension. Also, in bifactor analysis the expected dimensions were overruled by an overall explanatory general factor suggesting independence to be of particular importance for clinicians practicing resuscitation discussions in EDs. Studies to investigate how independence may relate to patients’ choice of resuscitation preference are needed.